Peranan Lembaga Zakat Dalam Pungutan Harta Zakat di Badan Amil Zakat Daerah Kabupaten Muaro Jambi - Idris, Isran; Yahya, Taufik (Jurnal Selat, 2018)
Zakat is an important element in Indonesian society and is one of the Islamic instruments used for the distribution of income and wealth. To realize this goal zakat requires an effective system of administration and must be organized by an institution that manages the collection and distribution affairs. Without an organized institution, the implementation of zakat will not be able to run smoothly and will realize a real difference in living standards among the community. The results showed that the Bazda charity institution had an effective role in channeling the productive zakat program and materially assisting in the social sector in the district of Muaro Jambi. In terms of income, there is an increase in the amount of zakat collection within 2 years since the establishment of Bazda in Muaro Jambi Regency. This indirectly shows that the increase in the number of zakat payers is increasing from time to time, but this increase is still not comparable to the number of Islamic communities who have the right to pay zakat. It is hoped that Bazda will look for alternatives so that in the following years it can collect other types of zakat to increase the amount of zakat funds and the need for programs that are right on target and efficient for the rightful zakat recipients. The factor of distribution of zakat is an influential factor and has a real impact in efforts to alleviate poverty and become an effective financial instrument in the problem of community capital in Muaro Jambi Regency.